Weaving at Black Mountain College : Anni Albers, Trude Guermonprez, and their students. - Beggs, Michael; Thomson, Julie J.; Arnal, Jeff (Asheville : Black Mountain College Museum and Arts Center, 2023)
In the mid-twentieth century, Black Mountain College attracted a remarkable roster of artists, architects, and musicians. Yet the weaving classes taught by Anni Albers, Trude Guermonprez, and six other faculty members are rarely mentioned or are often treated as mere craft lessons. This was far from the case: the weaving program was the school’s most sophisticated and successful design program. About ten percent of all Black Mountain College students took at least one class in weaving, including specialists like textile designers Lore Kadden Lindenfeld and Else Regensteiner, as well as students from other disciplines, like artists Ray Johnson and Robert Rauschenberg and architects Don Page and Claude Stoller. Drawing upon a wealth of unpublished material and archival photographs, Weaving at Black Mountain College rewrites history to show how weaving played a much larger role in the legendary art and design curriculum than previously assumed. The book illustrates dozens of objects from private and public collections, many of which have never been shown in this context. Essays explore connections and networks fostered by Black Mountain weavers; the ways in which weaving at the college was linked to larger discourses about weaving and craft; and Bauhaus influences transmitted by way of Anni Albers. The book also includes works by five contemporary artists that connect and respond to the legacy of weaving at Black Mountain College today.
Foreword -- Introduction -- Beginnings, 1933-1940 -- Specialization and Generalization, 1940-1947 -- Growth and Change, 1947-1956 -- Continuances, 1957-present -- Contemporary Connections
29.09.2023- 06.01.2024
boek
Keywords: Albers, Anni; Guermonprez, Trude